Effective bioremediation strategy for rapid in situ cleanup of anoxic marine sediments in mesocosm oil spill simulation - Genovese, Maria; Crisafi, Francesca; Denaro, Renata; Cappello, Simone; Russo, Daniela; Calogero, Rosario; Santisi, Santina; Catalfamo, Maurizio; Modica, Alfonso; Smedile, Francesco; Genovese, Lucrezia; Golyshin, Peter N.; et al. (Frontiers in Microbiology, 2014)
The purpose of present study was the simulation of an oil spill accompanied by burial of significant amount of petroleum hydrocarbons (PHs) in coastal sediments. Approximately 1,000 kg of sediments collected in Messina harbor were spiked with Bunker C furnace fuel oil (6,500 ppm). The rapid consumption of oxygen by aerobic heterotrophs created highly reduced conditions in the sediments with subsequent recession of biodegradation rates. As follows, after three months of ageing, the anaerobic sediments did not exhibit any significant levels of biodegradation and more than 80% of added Bunker C fuel oil remained buried. Anaerobic microbial community exhibited a strong enrichment in sulfate-reducing PHs-degrading and PHs-associated Deltaproteobacteria. As an effective bioremediation strategy to clean up these contaminated sediments, we applied a Modular Slurry System (MSS) allowing the containment of sediments and their physical-chemical treatment, e.g. aeration. Aeration for three months has increased the removal of main PHs contaminants up to 98%. As revealed by CARD-FISH, qPCR and 16S rRNA gene clone library analyses, addition of Bunker C fuel oil initially affected the activity of autochthonous aerobic obligate marine hydrocarbonoclastic bacteria (OMHCB), and after one month more than the third of microbial population was represented by Alcanivorax-, Cycloclasticus- and Marinobacter-related organisms. In the end of the experiment, the microbial community composition has returned to a status typically observed in pristine marine ecosystems with no detectable OMHCB present. Eco-toxicological bioassay revealed that the toxicity of sediments after treatment was substantially decreased. Thus, our studies demonstrated that petroleum-contaminated anaerobic marine sediments could efficiently be cleaned through an in situ oxygenation which stimulates their self-cleaning potential due to reawakening of allochtonous aerobic OMHCB.